Acceptance of sharia compliance implementation among hoteliers in the Klang Valley, Malaysia - Mohd, Adib (2021)
Tourism is a sector that the Government of Malaysia has recognized as an economic catalyst for the country. Islamic hospitality has become one of the attractive segments of the world's tourism industry, and, for many Islamic countries, it is a crucial income earner, especially for those providing services to Muslim travelers. Sharia Compliance Hotel has been created to cater to Muslim guests as demand and awareness for Islamic products and services has increased. There are three objectives in this research, (a) to evaluate the influence of attitude, subjective norm and perceived behavioural control on the acceptance of SCH implementation, (b) to assess the hoteliers’ level of understanding towards SCH attributes and (c) identify their level of awareness about SCH implementation in Malaysia. This research utilizes the Theory of Planned Behaviour (TPB) to investigate this issue. The data was collected using questionnaires distributed to 400 respondents working in hotels rated between three (3) to five (5) stars in the Klang Valley. Regression analysis and correlation result reveal a significant relationship between the factor of TPB and acceptance; furthermore, the results indicate that majority of the hoteliers are understood the SCH attributes and aware of SCH implementation in Malaysia.